Secukinumab for the treatment of palmoplantar psoriasis: a 2-year, multicenter, real-life observational study. (3rd April 2022) - Galluzzo, Marco; Talamonti, Marina; Atzori, Laura; Bardazzi, Federico; Campanati, Anna; Di Cesare, Antonella; Diotallevi, Federico; Flori, Maria Laura; Mugheddu, Cristina; Offidani, Annamaria; Piaserico, Stefano; Russo, Filomena; et al.
ABSTRACT: Background: Palmoplantar psoriasis is difficult to treat and often recalcitrant to conventional therapies. Clinical trials have demonstrated the efficacy and safety of secukinumab for this debilitating psoriasis form, but real-life evidence is currently limited. Therefore, here we described the outcomes of patients treated with secukinumab in clinical practice. Research Design and Methods: This was a real-life, retrospective, observational study involving patients with palmoplantar psoriasis treated with secukinumab (300 mg, subcutaneously) at seven dermatologic clinics in Italy. Treatment effectiveness was evaluated based on the changes of the Psoriasis Area and Severity Index (PASI) and palmoplantar (pp) PASI during treatment and by recording safety and tolerability issues over 104 weeks. Results: Forty-three patients initiated treatment with secukinumab. Previous treatments included topical and systemic therapies; half of patients had already tried one or more biologics. Secukinumab improved mean PASI rapidly and substantially with a 78.2% decrease at 16 weeks. Mean ppPASI also improved substantially, but more gradually, with reductions of 55.0% and 79.3% at 16 and 104 weeks, respectively. Approximately half of patients achieved complete skin clearance at 40 weeks. Secukinumab was well tolerated and no relevant treatment-related adverse events were reported. Conclusions: Secukinumab appears to be effective for the treatment of palmoplantar psoriasis also in the real-life setting.